2013
DOI: 10.1002/phar.1194
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Carboxylesterases in Drug Metabolism: Have We Overlooked Their Importance?

Abstract: Carboxylesterases are a multi-gene family of enzymes widely distributed throughout the body of mammals that catalyze the hydrolysis of esters, amides, thioesters, and carbamates. In humans, two carboxylesterases, hCE1 and hCE2, are important pathways of drug metabolism. Both are expressed in the liver, but levels of hCE1 greatly exceed those of hCE2. In the intestine only high levels of hCE2 are expressed. The most common drug substrates are ester prodrugs specifically designed to enhance oral bioavailability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
257
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(281 citation statements)
references
References 81 publications
3
257
2
6
Order By: Relevance
“…It has often been reported that CC is converted to candesartan by carboxylesterases via intestinal and hepatic first-pass metabolism (Miwa et al, 1998;Easthope and Jarvis, 2002); however, which isozymes of CES1 or CES2 are a major contributor remained unknown until now. Although Laizure et al (2013) supposed that CC is a CES2 substrate because of CC's large alcohol group of the prodrug moiety that CES2 prefers as a substrate, in the present study, the recombinant CES2 exhibited only low CC-hydrolase activity in contrast to rapid hydrolysis by the recombinant CES1. Moreover, the intestinal subcellular fractions showed minimal CC-hydrolase activity in all the species tested including humans, indicating negligible involvement of CES2, which had been reported to be expressed in the intestine in mice, rats, monkeys, and humans (Taketani et al, 2007;Satoh and Hosokawa, 2010).…”
Section: Discussioncontrasting
confidence: 42%
“…It has often been reported that CC is converted to candesartan by carboxylesterases via intestinal and hepatic first-pass metabolism (Miwa et al, 1998;Easthope and Jarvis, 2002); however, which isozymes of CES1 or CES2 are a major contributor remained unknown until now. Although Laizure et al (2013) supposed that CC is a CES2 substrate because of CC's large alcohol group of the prodrug moiety that CES2 prefers as a substrate, in the present study, the recombinant CES2 exhibited only low CC-hydrolase activity in contrast to rapid hydrolysis by the recombinant CES1. Moreover, the intestinal subcellular fractions showed minimal CC-hydrolase activity in all the species tested including humans, indicating negligible involvement of CES2, which had been reported to be expressed in the intestine in mice, rats, monkeys, and humans (Taketani et al, 2007;Satoh and Hosokawa, 2010).…”
Section: Discussioncontrasting
confidence: 42%
“…Although hCES1 and hCES2 have overlapping substrate recognition, clear evidence of ester-based substrate specificity has been observed (Satoh et al, 2002). In general, hCES1 accommodates substrates with a large acyl moiety whereas hCES2 favors substrates with a large alcohol substituent (Laizure et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many prodrugs are inactive compounds with carboxyl-ester, thio-ester, or amide (Taketani et al, 2007;Laizure et al, 2013), which are subsequently hydrolyzed to an active drug; the extent of hydrolysis markedly affects the pharmacologic activity and/or toxicity of these compounds. The intentional esterification to a prodrug has been used across different classes of drugs (e.g., antivirals, angiotensin-converting enzyme inhibitors) mostly to improve drug absorption and bioavailability (Imai, 2006;Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%